MR Imaging of the Hip: An Update on Bone Marrow Edema - Vassalou, Evangelia E.; Spanakis, Konstantinos; Tsifountoudis, Ioannis P.; Karantanas, Apostolos H. (Seminars in Musculoskeletal Radiology, 2019)
Bone marrow edema (BME) represents a frequent and easily detected MR imaging finding that is recognized as a common source of pain. It is considered a nonspecific finding that constitutes a central component of a wide spectrum of pathologies affecting the hip joint, showing high variability in terms of prognosis and treatment requirements. Solid knowledge of the various BME patterns and associated imaging findings indicative of these conditions can aid in differentiation. Additionally, correlation with clinical and laboratory data are essential for arriving at a final diagnosis in several cases. In this review, we describe the disease characteristics and imaging findings and also highlight the differential diagnostic clues regarding common hip disorders associated with BME including avascular necrosis, transient osteoporosis, stress injuries, and infectious/inflammatory disorders.
Keywords: bone marrow edema; hip; avascular necrosis; transient osteoporosis; MR imaging/diagnosis